Letter : Jesus and Julian Hickman Urrutia - Stokes, Richard R.
027-0023-001 RS/GMB. 32, Victoria Street, Westminster, S.W.1. 18th April, 1940. Your Ref. HVT/AC/100. Mr. H. V. Tewson, Trades Union Congress, Transport House, Smith Square, S.W.1. Dear Mr. Tewson, Julian and Jesus Hickman Urrutia. I have your letter of the 17th April and certainly will do what I can to help but you appreciate that the draughtsmen whom we employ are all rather of a specialised nature. Before therefore bothering to investigate the matter further would you please tell me whether either or both of them are fully qualified mechanical draughtsmen. The kind of goods that we make at one Works are big Mechanical Excavators, Mechanical Railway Equipment and so on and we need people to have a fairly extensive experience of mechanical detailing. In Scotland our demands are quite different; there we need people who have experience and knowledge of pressure vessels and boiler construction. If either of the men come under either of these two categories I will see what I can do to help them. Perhaps you would reply to me direct to *Ipswich where I go tomorrow and I should then be able to take the case up with the Chief Draughtsman. I am, Yours sincerely, Dick Stokes. *waterside works 292/946/27/23